Both the Survival Scenario and the Death Scenario Improve Memory Recall Regardless of the Processing/Priming Paradigm - Zhao, Xiaolin; Li, Hao; Zhang, Xinxin; Yang, Juan (Frontiers in Psychology, 2018)
Memory researchers have suggested human’s memory system can help us remember adaptive information conducive to survival and avoiding death. However, in previous studies, the “survival-” orienting task and the “death-” orienting task were adopted in different paradigms. Specifically, the survival-related task was adopted in a processing paradigm, in which participants were instructed to process words in terms of its relevance of survival value, while the death-related task was adopted in a priming paradigm, in which participants were first placed in a death-salient state, and then rated the pleasantness of each word without encoding its death value. The current study aimed to explore whether death scenarios improve recall as much as survival scenarios regardless of the processing/priming paradigm. In Experiment 1, we compared a survival scenario, a death scenario and a control scenario in both processing and priming paradigms. Our results showed that: (a) both survival-related thoughts and death-related thoughts could improve memory recall, both in processing and in priming paradigms; and (b) participants’ proportion of correct recall did not show difference between the survival and the death conditions. In Experiment 2, we used a more detailed control scenario and showed that both the death scenario and the survival scenario yielded higher recall than the control scenario in the priming paradigm. Together, our results suggest that both survival and death scenarios have a similar effect on memory recall regardless of the processing/priming paradigms.